The Effect of Service Quality, Price, and Facilities on Customer Satisfaction at Warkop 08 - Muhammad Saeed Asshihab; Ocdy Amelia; Muhammad Dharma Tuah Putra Nasution (Yayasan Cita Cendikiawan Al Kharizmi, 2026)
This study was conducted to determine the effect of service quality, price, and facilities on customer satisfaction at Warkop 08. This study used a quantitative approach with primary data selected using simple random sampling. The data analysis technique used was multiple linear regression, preceded by classical assumption testing and hypothesis testing. The results of this study demonstrate that service quality, price, and facilities have a positive effect on customer satisfaction, both partially and simultaneously. The coefficient of determination (R²) of 0.754 indicates that the variables of service quality, price, and facilities account for 75.4% of the variation in customer satisfaction levels. Meanwhile, the remaining 24.6% is influenced by other factors not included in this study. Thus, efforts to improve service quality, implement appropriate pricing, and provide adequate facilities need to be prioritized because they play a crucial role in enhancing customer satisfaction. This study is intended to serve as a reference for business managers in formulating strategies to improve customer satisfaction and business competitiveness.